Sequential Explicit and Implicit Coupling of 3D Compositional Reservoir, Wells and Surface Facility - Bik Deli, Alireza (2021)
Petroleum production systems consist of three integrated individual elements: subsurface reservoir, wells, and surface facility. The design, construction, and maintenance of surface facility for hydrocarbon production require simulation studies. These studies become much more realistic when well and surface facility are simulated together with the subsurface reservoir. The main objective of this thesis is to develop a framework to model the compositional multiphase/multicomponent fluid flow from reservoir, wells, and surface facility using flow tables to evaluate the pressure loss through wells and pipes. The framework is integrated to the multiphase/multicomponent compositional reservoir simulator called UTCOMPRS from the University of Texas at Austin. Two new frameworks have been developed for UTCOMPRS. The first is sequential explicit coupling and the second is sequential implicit coupling. Among three approaches for pressure drop calculation along the tubing, including the homogenous model, drift flux model, and a pre-calculated table; the main focus here is concentrated on the last method. For sequential explicit coupling, three classes of flow tables were developed and validated with a commercial simulator, which works in conjunction with the IMPEC (Implicit Pressure Explicit Composition) reservoir formulation. Also, some additional tools for controlling, and reporting the integrated models are described. Different case studies of this work demonstrated various production scenarios on the developed framework for 2D and 3D reservoirs. The accuracy of the developed framework is highly dependent on the interpolation of the bottom hole pressure and the injector constraint activation, among other operational parameters. A new tool called connection tables has been developed for sequential implicit coupling. This table processes the data, features, and map of the surface facility. With as many unknowns as the user requires, the connection table can be consistent. The mathematical explanation of the connection table is also given for each segment's condition, whether it be a flow equation or a flow table. The simulator can generate the surface facility configuration without the use of a third-party simulator once the connection table is supplied to it.